Community-Based Research on Urban farming: Towards Sustainable Development and Inclusive Urban Design in Masangan Kulon Village, Indonesia - Prianto, Kusnul; Umam, Muchamad Helmi; Ernawati, Rita; Ulinuha, Muhammad; Rosidi, Ayu Kanaya (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This study investigates the use of Urban farming in Masangan Kulon Village, Indonesia, using a Community-Based Research (CBR) paradigm. Community emotions surrounding village life were collected through surveys and participatory involvement, uncovering opportunities and problems for the growth of urban farming. The public facility land, situated strategically within the Griya Bhayangkara housing neighborhood, has emerged as an ideal location for agricultural activity. The development plan tackled various challenges, such as enhancing infrastructure and promoting community engagement, while emphasizing the significance of inclusive urban design planning. Despite the COVID-19 pandemic, the community has shown resilience by converting public spaces for agricultural use. The proposed action plan prioritizes community engagement, improving infrastructure, and promoting environmental sustainability. The proposed action plan will support the development of sustainable Urban farming and advocate for inclusive urban design planning methods